Efficacy and safety of a patch vaccine containing heat-labile toxin from Escherichia coli against travellers' diarrhoea: a phase 3, randomised, double-blind, placebo-controlled field trial in travellers from Europe to Mexico and Guatemala - Behrens, Ronald H; Cramer, Jakob P; Jelinek, Tomas; Shaw, Hilary; von Sonnenburg, Frank; Wilbraham, Darren; Weinke, Thomas; Bell, David J; Asturias, Edwin; Pauwells, Hermann L Enkerlin; Maxwell, Roberto; Paredes-Paredes, Mercedes; et al. (The Lancet infectious diseases, 2014)
Enterotoxigenic Escherichia coli (ETEC) is a major cause of travellers' diarrhoea. We investigated the efficacy and safety of a skin-patch vaccine containing the pathogen's heat-labile toxin (LT) in a population of travellers to Mexico and Guatemala. In this phase 3, randomised, double-blind, placebo-controlled field trial, healthy adults (aged 18–64 years) travelling from Germany or the UK to Mexico or Guatemala were assigned in a 1:1 ratio by a dynamic electronic randomisation system to receive transcutaneous immunisation with a patch containing 37·5 μg of ETEC LT or a placebo patch. Participants, site staff, and the investigators who did the analyses were masked to group assignment. Participants were vaccinated before travel, with two patches given 14 days apart. In the destination country, participants tracked stool output in a diary and provided stool samples for pathogen identification if diarrhoea occurred. The primary endpoint was the proportion of participants with at least one episode of moderate-to-severe diarrhoea (defined as four or more unformed stools in a 24 h period) in which either or both ETEC enterotoxins (LT and heat-stable toxin [ST]) were detected. The study is registered at ClinicalTrials.gov, number NCT00993681. 2036 participants were recruited and randomly assigned between Oct 14, 2009, and Aug 13, 2010, with 1016 allocated to receive the LT patch and 1020 the placebo patch. 821 participants in the LT-patch group and 823 in the placebo group received both vaccinations and were analysed in the per-protocol population. 30 (3·7%, 95% CI 2·5–5·2) participants in the LT-patch group and 46 (5·6%, 4·1–7·4) in the placebo group had moderate or severe ETEC diarrhoea (vaccine efficacy 34·6%, −2·2 to 58·9; p=0·0621). 9333 local (ie, patch-site) adverse events (including erythema, rash, pruritus, hyperpigmentation, pain, hypopigmentation, and oedema) occurred in 943 (93%) of 1015 participants in the LT-patch group, compared with 1444 local adverse events in 574 (56%) of 1019 participants in the placebo group (p<0·0001). Serious adverse events occurred in 25 participants (14 in the LT-patch group and 11 in the placebo group), with all regarded as either unrelated or possibly related to treatment. Vaccine-induced hyperpigmentation persisted for at least 180 days after vaccination in 150 (18%) of the 849 participants who received both vaccinations and returned for final assessment in the LT-patch group, compared with none of the 842 participants in the placebo group. The vaccine was immunogenic, with a post-vaccination geometric mean titre of LT-specific serum immunoglobulin G of 3400·29, compared with 315·41 in the placebo group. Although the LT antigen was delivered effectively by the skin patch, the vaccine did not protect travellers against diarrhoea caused by ETEC or other organisms. Future vaccines against travellers' diarrhoea might need to include several antigens against various diarrhoeal pathogens, and might need to be able to generate mucosal and higher systemic immunity. Intercell USA.